Earthquake and Tsunami Emergency Preparedness of Visually Disabled People - Fatin, Mutia; Sofia, Sofia; Oktari, Rina Suryani (International Journal of Disaster Management, 2020)
This study aims to assess the level of preparedness of visually disabled people in terms of the emergency response plan for earthquake and tsunami. This study uses analytical methods, cross-sectional design, and questionnaires as data collection tools. The sample of this study was 54 visually disabled people who were living in Banda Aceh. The analysis revealed that the level of preparedness of the emergency response plan, the majority of visually disabled people has a low level of preparedness to plan an emergency response (63%), especially the total blindness group (46.3%). The Mann-Whitney test results showed that there was a statistically significant relationship between the visual impairment group and total blindness group on the preparedness of the emergency response plan (p = 0.016). Hence, this study suggests some recommendations, including a disaster preparedness program that is sensitive to people with disabilities, increasing the participation of people with disabilities in DRR education, and increasing the accessibility of people with disabilities to DRR teaching/learning materials.